Management model of efficiency of electric energy consumption by airports - Захарченко, Віктор Панасович; Соколова, Наталія Петрівна (Eastern-European Journal of Enterprise Technologies, 2014)
The paper describes a system management model of efficient electric energy consumption by airports, which is based on the improved classical closed-loop management scheme. With the aim of efficient electric energy consumption management, it is proposed to organize a separate energy management service in airports. Information and managerial relationships between the energy management service and airport departments are determined. Management system efficiency is based on the improved methods and algorithms on the regulation of specific electric energy consumption and forecasting of the amount of electric energy consumption by airport objects. The improved regulation method will allow to determine appropriate specific consumption standards for airports for a basic period. The regulation of specific electric energy consumption by airport objects will allow to determine their power-consuming zones and first of all regulate their electric energy consumption efficiency. A system for multifactor forecasting of electric energy consumption by airport objects will allow to execute electric energy consumption management by reducing specific electric energy consumption for the forecast period. The efficiency of these measures is increased through the step-by-step implementation of the complex of practical recommendations. Using the model allows to improve the airport efficiency, which confirms the relevance and practical value of the given study.